Outdoor Fieldwork in Higher Education: Learning From Multidisciplinary Experience. (March 2018) - Munge, Brendon; Thomas, Glyn; Heck, Deborah
Background: Many disciplines use outdoor fieldwork (OFW) as an experiential learning method in higher education. Although there has been an increase in research into the pedagogical approaches of OFW, the use of OFW is contested.Purpose: The purpose of the study was to synthesize the OFW literature across a range of disciplines to identify common strengths, weaknesses, opportunities, and threats (SWOT) and outline implications for how OFW is used as an experiential learning pedagogy in higher education.Methodology/Approach: A descriptive literature review was undertaken to examine each aspect of the SWOT at the micro, meso, and macro levels, drawing from disciplines using OFW including biology, outdoor and environmental education, archaeology, and the associated geosciences.Findings/Conclusions: Strengths of OFW include engagement, outreach, and professional competencies; weaknesses exist in the areas of equity, logistics, and standards. Opportunities include improving pedagogical practices, diversity, and collaboration, while threats to OFW were costs, funding, outdated practices, and governance.Implications: Academics from a range of disciplines using OFW have similar experiences; therefore, exploring ways to collaborate or learn from each other will further develop OFW as an experiential learning strategy in higher education.